A Field Study Using Some Properties and Applications of Soft ii-Open Sets - Aveen Dawod; Sabih Askandar (College of Education for Pure Sciences, 2024)
In this research, we presented a new method for collecting data and performing calculations to obtain the required results differently from what have been studied before. In the beginning, we introduce new types of soft sets in soft topological spaces, explaining many properties such as soft ii-dense sets, soft ii-connectedness, soft ii-perfection, and soft ii-compactness. We proved that any soft set (S,E) could be soft ii-connected in (X,τ,E) when it is soft ii-connected in a soft partial sub-space ), In addition, we used the concept of soft topology in calculating the cost of service projects in several areas of the town of Bashiqa, in the Nineveh Governorate/north of Iraq, this project was achieved either in a specific region or several regions by using the theorem of soft sets in soft topological spaces. Infrastructure projects were undertaken in the areas of Bashiqa, Al-Darwish, Baibukht, and the villages of Al-Fadhiliya and Omar Qabji. Such as paving and covering various roads, building schools, and health centers, and extending groundwater networks.